A COMPARATIVE STUDY OF USER EXPERIENCE AND SATISFACTION ON SWIGGY AND ZOMATO IN TIRUNELVELI DISTRICT - T. Krishnaveni; P. Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The emergence of food delivery platforms has changed consumer dining behavior in urban and semi urban areas of India. The present study presents a comparison of user experience and satisfaction in two leading food delivery platforms (Swiggy and Zomato) in Tirunelveli District; the purpose is to show which platform is preferred; to measure how satisfied users are with each platform across service parameters such as delivery time, food quality, app interface, customer support, promotional offers and to ascertain major factors that influence user choice of platform for food delivery. Using structured questionnaire, 187 regular users of food delivery platforms were surveyed; data was analyzed using percentage analysis, weighted average, Garrett ranking, t-tests and chi-square tests. Results showed that Swiggy had a slight preference over Zomato, both platforms scored well with delivery time and food quality but customer support needed improvement, moreover, results indicated that there was no significant difference between satisfaction levels for the two platforms, and that there was no association between platform preference and gender. The findings would provide food delivery executives with some information on improvements needed, and could also be useful for determining customer loyalty in a growing food delivery market.